Bio-Psycho-Socio-Spirito-Cultural Factors of Burnout: A Systematic Narrative Review of the Literature - Listopad, Ian W.; Michaelsen, Maren M.; Werdecker, Lena; Esch, Tobias (Frontiers in Psychology, 2021)
Background: Burnout is a widespread, multifactorial, and mainly psychological phenomenon. The pathogenesis of burnout is commonly described within the bio-psycho-social model of health and disease. Recent literature suggests that the phenomenon of burnout may be broader so that the three dimensions might not reflect the multifaceted and complex nature of the syndrome. Consequently, this review aims to identify the diversity of factors related to burnout, to define superordinate categories based on these, and to clarify whether the bio-psycho-social model adequately describes the pathogenesis of burnout – holistically and sufficiently. Method: Five online databases (PubMed, PubPsych, PsychARTICLES, Psychology and Behavioral Sciences Collection, and Google Scholar) were systematically searched using defined search terms to identify relevant studies. The publication date was set between January 1981 and November 2020. Based on the selected literature, we identified factors related to burnout. We aggregated these factors into a comprehensible list and assigned them to overarching categories. Then, we assigned the factors to the dimensions of an extended model of health and disease. Results: We identified a total of 40 burnout-related factors and 10 overarching categories. Our results show that in addition to biological, psychological, and social factors, various factors that can be assigned to a spiritual and work cultural dimension also plays an important role in the onset of burnout. Conclusion: An extended bio-psycho-socio-spirito-cultural model is necessary to describe the pathogenesis of burnout. Therefore, future studies should also focus on spiritual and work cultural factors when investigating burnout. Furthermore, these factors should not be neglected in future developments of diagnosis, treatment, and prevention options.